Performance Analysis of Trellis Coded Modulation and Diversity Combining on Wireless Channel. Issue 1 (January 2021) - Baharuddin,; Andre, H; Muharam, M; Luthfi, A; Angraini, R
Abstract: The use of trellis coded modulation (TCM) and diversity maximal ratio combining (MRC) are applied in this research in order to overcome the impairment of information signals caused by fading and noise. TCM is chosen due to its ability to correct error without increasing the transmit power and channel bandwidth. MRC is used to obtain multiple data streams corresponding to the transmitted image at the receiver. The testing of the system is carried out by calculating peak signal to noise ratio (PSNR) and bit error rate (BER). The result of this simulation shows that the use of TCM and MRC in the image transmission system improves significantly compare to the system which only use TCM without MRC.